2009
DOI: 10.1287/orsc.1090.0439
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning from Extreme Performance Experience: The Impact of Success and Recovery Experience

Abstract: This paper argues that two different types of a firm's own extreme performance experiences—success and recovery—and their interactions can generate survival-enhancing learning. Although these types of experience often represent valuable sources of useful learning, several important learning challenges arise when a firm has extremely limited prior experience of the same type. Thus, we theorize that a certain threshold of a given type of experience is required before each type of experience becomes valuable, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 86 publications
5
111
0
3
Order By: Relevance
“…We find that individuals with a greater number of prior successes are more able to learn from their failures than those with fewer successes, a result consistent with the findings of Kim et al (2009) at the organizational level. Our effect may be a result of reduced self-threat, additional knowledge, or associative learning.…”
Section: Discussion Of Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We find that individuals with a greater number of prior successes are more able to learn from their failures than those with fewer successes, a result consistent with the findings of Kim et al (2009) at the organizational level. Our effect may be a result of reduced self-threat, additional knowledge, or associative learning.…”
Section: Discussion Of Resultssupporting
confidence: 87%
“…Combined with the knowledge gained through failure, an individual can work through the process of creating and then testing new hypotheses. Finally, research on associative learning offers evidence as to why prior success may help individuals respond to failure (Sternberg 2003;Kim, Kim and Miner 2009). When failure occurs after a series of successes, it marks a salient deviation that may be noticed precisely because of its salience (Taylor and Fiske 1978).…”
Section: Hypothesis 2: the Prior Failures Of Other Workers Have A Grementioning
confidence: 99%
“…For example, unlike day-to-day operational issues where there are evident gains from the repetition of tasks (Thompson 2009), developing and implementing strategies to about how to enter a market, thwart the competition, or meet consumer needs are infrequent occurrences. Consequently, this increases the likelihood of founders basing their decisions on small sample sizes which limits opportunities to apply relevant evidence to the current situation (Kim et al 2009). Inferential errors are also likely because individuals tend to focus on successful rather than unsuccessful outcomes.…”
Section: The Maladaptive Effects Of Habitual Experiencementioning
confidence: 99%
“…Second, individuals are prone to cognitive biases such as over-optimism or over-confidence. The asymmetry between subjective beliefs about ability and actual ability adds to the likelihood of dysfunctional outcomes (Kim et al 2009). Finally, individuals struggle to identify outcomes because it is difficult to specify the dimensions of success or failure (Zollo 2009).…”
mentioning
confidence: 99%
“…Success stories reveal possible practices worth adopting, whereas failure stories save teams from implementing practices that would stall or reverse their improvement efforts. Organizational learning research suggests that both types of knowledge-knowledge of do's and don'ts-are valuable for teams and organizations striving to implement new and better processes in a timely manner (Kim, Kim, & Miner, 2009). Hansen (1999) found that new-product development teams that leveraged their external ties performed better on their projects.…”
Section: Inter-olas and Performancementioning
confidence: 99%